Point-valued mappings of sets - Matt Insall (International Journal of Mathematics and Mathematical Sciences)
Let X be a metric space and let CB(X) denote the closed bounded subsets of X with the Hausdorff metric. Given a complete subspace Y of CB(X), two fixed point theorems, analogues of results in [1], are proved, and examples are given to suggest their applicability in practice.